Entropy method in the models industrial process control - Azarenkov, N. A.; Pihnastyi, O. M.; Khodusov, V. D. (Національний технічний інститут "Харківський політехнічний інститут", 2013)
For the first time, the importance of the entropy method in control theory has Dzh. Fon Neumann. Entropy approach to modeling the processes discussed in detail B. N. Petrov, I. V. Prangishvili. The entropy of the process is associated with the distribution function of process parameters on the possible states. The distribution function of the items of work is not explicitly linked to the parameters describing the state of the items of work in the technological processing.
Keywords: production line; PDE-model of production; PDE-model flow production; PDE production model